Pengaruh Fear of Missing Out (FOMO) dan Intensitas Penggunaan Media Sosial Terhadap Impulsive Buying Belanja Online pada Wanita Menikah - Cahyani Lahay; Lania Muharsih; Yuwono Pratomo (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of Fear of Missing Out (FOMO) and social media usage intensity on impulsive buying in online shopping among married women in Kota Wisata Housing, Bogor. The background is based on the increasing phenomenon of impulsive buying in e-commerce, particularly triggered by FOMO and intense social media exposure among married women. This study uses a quantitative method with an associative causality research design. The sampling technique used is non-probability sampling with a purposive sampling method. The population was married women domiciled in Kota Wisata Cibubur Housing and actively engaged in online shopping, with 209 respondents. The research instruments consisted of a FOMO scale adopted from the FoMO Scale by Przybylski et al (2013), a social media usage intensity scale adopted from the Media and Technology Usage and Attitudes Scale (MTUAS) by Rosen et al (2013), and an impulsive buying scale adopted from the Buying Impulsiveness Scale by Rook & Fisher (1995). The results showed that simultaneously, both variables have a significant effect on impulsive buying (F = 183.330, p < 0.05) with 64% contribution (R² = 0.640). Partially, FOMO has a significant effect on impulsive buying (t = 10.576, p < 0.05), and social media usage intensity also has a significant effect on impulsive buying (t = 9.708, p < 0.05). The conclusion is that the higher the level of FOMO and social media usage intensity, the higher the impulsive buying behavior among married women in Kota Wisata Housing, Bogor.